Source-to-sink and evolutionary processes of the East China Sea inner-shelf mud belt and its response to environmental changes since the Holocene: New evidence from the distal mud belt. (July 2021) - Cong, Jingyi; Hu, Gang; Jonell, Tara N; Zhang, Yong; Li, Yuting; Bi, Shipu
During the past decades, the elongated mud belt, 1000 km length, in the inner shelf of the East China Sea (ECS), has been extensively studied. Previous studies mainly focused on the northern part of the mud belt. There are still many arguments on various issues of the mud belt, including the provenance discrimination, the formation mechanism, and its evolution response to climate and environmental changes. In this paper, a borehole acquired from the distal southern mud belt which penetrated the Holocene strata with the collected data was analyzed. According to the parameters of (La/Sm)UCC versus (Gd/Yb)UCC and the ternary diagram of smectite-illite-(kaolinite + chlorite), sediments from the top section of Core ECS1601 originated from the Yangtze River since 13.7 ka. Sediments from upper and lower reaches of the Yangtze River can be clearly distinguished by (Gd/Yb)UCC value. The provenance of the distal mud belt shifted from upper reaches to lower valley since 5 ka and returned to the upper reaches again since 2.5 ka, which was related to the asynchronous evolution of Asian monsoon system and anthropogenic activities. The high sedimentation rates occurring in the distal mud belt between 5 and 2.5 ka were related to the decreased sediment supply of the upper reaches and the strengthened Zhejiang-Fujian Coastal Current (ZFCC) caused by the intensified East Asian Winter Monsoon (EAWM).